ICT Enabled Service Delivery System in India: An Overview: The Role of Information and Communication Technology in Improving Service Delivery in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Information and Communication Technology (ICT) would have a prominent and progressive role in the new era as the single most important enabler for improving efficiency and effectiveness in the services delivery system in an organisation or a nation. Being in the same era, India too incorporated information and communication technology as a driver of services delivery to the public. An attempt has been made in this paper to capture the overview of ICT enabled services following with the merit and limitations and conclusion at last.